Central role of dynamic tidal biofilms dominated by aerobic hydrocarbonoclastic bacteria and diatoms in the biodegradation of hydrocarbons in coastal mudflats - Coulon, Frederic; Chronopoulou, P-M; Fahy, A; Païssé, S; Goñi-Urriza, M; Peperzak, L; Acuña, Alvarez L; McKew, BA; Brussaard, CPD; Underwood, GJC; Timmis, KN; Duran, R; et al. (American Society for Microbiology, 2012)
Mudflats and salt marshes are habitats at the interface of aquatic and terrestrial systems that provide valuable services to ecosys- tems. Therefore, it is important to determine how catastrophic incidents, such as oil spills, influence the microbial communities in sediment that are pivotal to the function of the ecosystem and to identify the oil-degrading microbes that mitigate damage to the ecosystem. In this study, an oil spill was simulated by use of a tidal chamber containing intact diatom-dominated sediment cores from a temperate mudflat. Changes in the composition of bacteria and diatoms from both the sediment and tidal biofilms that had detached from the sediment surface were monitored as a function of hydrocarbon removal. The hydrocarbon concen- tration in the upper 1.5 cm of sediments decreased by 78% over 21 days, with at least 60% being attributed to biodegradation. Most phylotypes were minimally perturbed by the addition of oil, but at day 21, there was a 10-fold increase in the amount of cyanobacteria in the oiled sediment. Throughout the experiment, phylotypes associated with the aerobic degradation of hydro- carbons, including polycyclic aromatic hydrocarbons (PAHs) (Cycloclasticus) and alkanes (Alcanivorax, Oleibacter, and Oceano- spirillales strain ME113), substantively increased in oiled mesocosms, collectively representing 2% of the pyrosequences in the oiled sediments at day 21. Tidal biofilms from oiled cores at day 22, however, consisted mostly of phylotypes related to Alcaniv- orax borkumensis (49% of clones), Oceanospirillales strain ME113 (11% of clones), and diatoms (14% of clones). Thus, aerobic hydrocarbon biodegradation is most likely to be the main mechanism of attenuation of crude oil in the early weeks of an oil spill, with tidal biofilms representing zones of high hydrocarbon-degrading activity.